Home My Page Projects Code Snippets Project Openings diderot
 Summary Activity Tracker Tasks SCM

# SCM Repository

[diderot] Diff of /branches/ein16/src/compiler/high-il/normalize-ein.sml
 [diderot] / branches / ein16 / src / compiler / high-il / normalize-ein.sml

# Diff of /branches/ein16/src/compiler/high-il/normalize-ein.sml

branches/charisee/src/compiler/high-il/normalize-ein.sml revision 2508, Tue Nov 12 17:14:33 2013 UTC branches/charisee_dev/src/compiler/high-il/normalize-ein.sml revision 3678, Mon Feb 15 19:36:00 2016 UTC
# Line 4  Line 4
4      local      local
5
6      structure E = Ein      structure E = Ein
7  (*    structure P=Printer      structure P=Printer
8      structure O =OrderEin*)      structure F=Filter
9      in      structure G=EpsHelpers
10        structure Eq=EqualEin
11        structure R=RationalEin
(*Flattens Add constructor: change, expression *)
fun flatten((i, (E.Add l)::l'))= flatten(1,l@l')
|flatten(i,((E.Const c):: l'))=
if (c>0.0 orelse c<0.0) then let
val(b,a)=flatten(i,l') in (b,[E.Const c]@a) end
else flatten(1,l')
| flatten(i,[])=(i,[])
| flatten (i,e::l') =  let
val(b,a)=flatten(i,l') in (b,[e]@a) end

val (b,a)=flatten(0,e)
in case a
of [] => (1,E.Const(1.0))
| [e] => (1,e)
| es => (b,E.Add es)
(* end case *)
end

fun mkProd [e]=(1,e)
| mkProd(e)=let
fun flatten(i,((E.Prod l)::l'))= flatten(1,l@l')
|flatten(i,((E.Const c)::l'))=
if(c>0.0 orelse  0.0>c) then (3,[E.Const 0.0])
else flatten(i,l')
| flatten(i,[])=(i,[])
| flatten (i,e::l') =  let val(a,b)=flatten(i,l') in (a,[e]@b) end
val (change,a)=flatten(0,e)
in if(change=3) then (1,E.Const(0.0))
else case a
of [] => (1,E.Const(0.0))
| [e] => (1,e)
| es => (change, E.Prod es)
(* end case *)
end

(* filter function shifts constant/greeks to outside product*)
fun filter([],pre,dels,post)=(pre,dels,post)
| filter(E.Const c::es, pre, dels,post)=filter(es, pre@[E.Const c],dels,post)
| filter(E.Delta d::es,pre,dels,post)=filter(es,pre,dels@[E.Delta d],post)
| filter(E.Value v::es, pre, dels,post)=filter(es, pre@[E.Value v],dels,post)
| filter(E.Epsilon e::es, pre,dels, post)=filter(es, pre@[E.Epsilon e],dels,post)
| filter(E.Tensor(id,[])::es, pre, dels,post)=filter(es, pre@[E.Tensor(id,[])],dels,post)
| filter(E.Prod p::es, pre,dels, post)=filter(p@es,pre,dels,post)
| filter(e::es, pre,dels, post)= filter(es, pre, dels,post@[e])
12
13        in
14
15        val testing=0
16        fun err str=raise Fail (String.concat["Ill-formed EIN Operator",str])
17        fun mkProd e= F.mkProd e
18        fun filterSca e=F.filterSca e
20        fun filterGreek e=F.filterGreek e
21        fun mkapply e= derivativeEin.mkapply e
22        fun testp n=(case testing
23            of 0=> 1
24            | _ =>(print(String.concat n);1)
25        (*end case*))
26
27        val zero=E.B(E.Const 0)
28        fun setConst e = E.setConst e
29        fun setNeg e  =  E.setNeg e
30        fun setExp e  =  E.setExp e
31        fun setDiv e= E.setDiv e
32        fun setSub e= E.setSub e
33        fun setProd e= E.setProd e
35
36  fun prodPartial ([e1],p1)= E.Prod[E.Partial p1,e1]      (*mkSum:sum_indexid list * ein_exp->int *ein_exp
37    | prodPartial((e1::e2),p1)=let      *distribute summation expression
38      val l= prodPartial(e2,p1)      *)
39      val (_,e2')= mkProd[e1,l]      fun mkSum(sx1,b)=(case b
40      val (_,e1')=mkProd(e2@ [E.Partial p1, e1])          of E.Lift e         => (1,E.Lift(E.Sum(sx1,e)))
41      in          | E.Tensor(_,[])    => (1,b)
42          E.Add[e1',e2']          | E.B _             => (1,b)
43      end          | E.Opn(E.Prod, es)   => filterSca(sx1,es)
44            | _                 => (0,E.Sum(sx1,b))
45            (*end case*))
46
47  fun prodAppPartial ([e1],p1)= E.Apply(E.Partial p1,e1)      (*mkprobe:ein_exp* ein_exp-> int ein_exp
48    | prodAppPartial((e1::e2),p1)=let      *rewritten probe
49      val l= prodAppPartial(e2,p1)      *)
50      val (_,e2')= mkProd[e1,l]      fun mkprobe(b,x)=let
51      val (_,e1')=mkProd(e2@ [E.Apply(E.Partial p1, e1)])          val (c,rtn)=(case b
52                of (E.B _)              => (0,b)
53                | E.Tensor _            => err("Tensor without Lift")
54                | E.G _                 => (0,b)
55                | E.Field _             => (0,E.Probe(b,x))
56                | E.Lift e1             => (1,e1)
57                | E.Conv _              => (0,E.Probe(b,x))
58                | E.Partial _           => err("Probe Partial")
59                | E.Apply _             => (0,E.Probe(b,x))
60                | E.Probe _             => err("Probe of a Probe")
61                | E.Value _             => err("Value used before expand")
62                | E.Img _               => err("Probe used before expand")
63                | E.Krn _               => err("Krn used before expand")
64                | E.Sum(sx1,e1)         => (1,E.Sum(sx1,E.Probe(e1,x)))
65                | E.Op1(op1, e1)        => (1,E.Op1(op1, E.Probe(e1,x)))
66                | E.Op2(op2, e1,e2)     => (1,E.Op2(op2, E.Probe(e1,x), E.Probe(e2,x)))
67                | E.Opn(opn, [])        => err("Probe of empty operator")
68                | E.Opn(opn, es)        => (1,E.Opn(opn, List.map(fn e1=> E.Probe(e1,x)) es))
69                (*end case*))
70      in      in
72      end      end
73
74        (* normalize: EIN->EIN
75        * rewrite body of EIN
76        * note "c" keeps track if ein_exp is changed
77        *)
78        fun normalize (ee as Ein.EIN{params, index, body},args) = let
79          val changed = ref false
80          fun rewrite body =let
81
82            fun prod2(e1, e2,[]) =
83            (case (rewrite e1, rewrite e2)
84  (*remove eps Index*)          of (E.B(E.Const 0), e2') => (changed:=true;e2')
85  fun rmEpsIndex(i,[],rest)=rest          | (e1', E.B(E.Const 0)) => (changed:=true;e1')
86    | rmEpsIndex(i, (E.V c ,lb, ub)::es,rest)=          | (e1', e2') => E.Opn(E.Prod,[e1',e2']))
87      if (i=c) then rest@es          | prod2(e1, e2,es) = let
88      else rmEpsIndex(i, es, rest@[(E.V c, lb, ub)])          val e2= E.Opn(E.Prod,e2::es)

(*remove index variable from list*)
fun rmIndex(_,_,[])=[]
| rmIndex([],[],cs)=cs
| rmIndex([],m ,e1::cs)=[e1]@rmIndex(m,[],cs)
| rmIndex(i::ix,rest ,(c,lb,ub)::cs)=
if(i=c) then rmIndex(rest@ix,[],cs)
else rmIndex(ix,rest@[i],(c,lb,ub)::cs)

(* Transform eps to deltas*)
fun epsToDels(E.Sum(count,E.Prod e))= let
fun doubleEps((E.Epsilon (a,b,c))::(E.Epsilon(d,e,f))::es,eps,e3)=
let

(*Function is called when eps are being changed to deltas*)
fun createDeltas(i,s,t,u,v, e3)= let

(*remove index from original index list*)

val s'= rmEpsIndex(i,count,[])

val deltas= E.Sub(
E.Prod([E.Delta(E.V s,E.V u), E.Delta(E.V t,E.V v)] @e3),
E.Prod([E.Delta(E.V s,E.V v), E.Delta(E.V t,E.V u)]@e3))

in (case (eps,es,s')
of ([],[],[]) =>(1,deltas)
|([],_,[]) =>(1,E.Prod( es@[deltas]))
|([],[],_)=>(1,E.Sum(s',deltas))
|([],_,_)=>(1,E.Sum(s',E.Prod(es@[deltas])))
|(_,_,[])=>(1,E.Prod(eps@es@[deltas]))
|_ =>(1, E.Sum(s', E.Prod(eps@es@[deltas])))
)
end

in if(a=d) then createDeltas(a,b,c,e,f, e3)
else if(a=e) then createDeltas(a,b,c,f,d, e3)
else if(a=f) then createDeltas(a,b,c,d,e, e3)
else if(b=d) then createDeltas(b,c,a,e,f, e3)
else if(b=e) then createDeltas(b,c,a,f,d,e3)
else if(b=f) then createDeltas(b,c,a,d,e,e3)
else if(c=d) then createDeltas(c,a,b,e,f,e3)
else if(c=e) then createDeltas(c,a,b,f,d,e3)
else if(c=f) then createDeltas(c,a,b,d,e,e3)
else (0,E.Const 0.0)
end
fun findeps(e,[])= (e,[])
| findeps(e,(E.Epsilon eps)::es)=  findeps(e@[E.Epsilon eps],es)
| findeps(e,es)= (e, es)

fun dist([],eps,rest)=(0,eps,rest)
| dist([e],eps,rest)=(0,eps@[e],rest)
| dist(c1::current,eps,rest)=let
val(i, exp)= doubleEps(c1::current,eps,rest)
in  (case i of 1=>(i,[exp],[E.Const 2.0])
|_=> dist(current, eps@[c1],rest))
end

val (es,rest)=findeps([],e)
89      in      in
90          dist(es,[],rest)          (case (rewrite e1, rewrite e2)
91            of (E.B(E.Const 0), _) => (changed:=true;E.B(E.Const 0))
92            | (_ , E.B(E.Const 0)) => (changed:=true;E.B(E.Const 0))
93            | (e1', E.Opn(E.Prod, ps')) => E.Opn(E.Prod, e1'::ps')
94            | (e1', e2') =>(changed:=true; E.Opn(E.Prod,[e1',e2']))
95            (*end case*))
96      end      end
97
98  (*Another strategy. Go through entire expression inside summation and jsut examine index to apply deltas*)          in (case body
99            of E.B _                                => body
100  (* Apply deltas to tensors/fields*)          | E.Tensor _                            => body
101  fun reduceDelta(E.Sum(c,E.Prod p))=let          | E.G _                                 => body
102                    (************** Field Terms **************)
103      fun findDeltas(dels,rest,E.Delta d::es)= findDeltas(dels@[E.Delta d], rest, es)          | E.Field _                             => body
104      | findDeltas(dels,rest,E.Epsilon eps::es)=findDeltas(dels,rest@[E.Epsilon eps],es)          | E.Lift e1                             => E.Lift(rewrite e1)
105      | findDeltas(dels,rest,es)=  (dels,rest,es)          | E.Conv _                              => body
106            | E.Partial _                           => body
107      fun distribute(change,d,dels,[],done)=(change,dels@d,done)          | E.Probe(e1,e2)              =>
| distribute(change,[],[],e,done)=(change,[],done@e)
| distribute(change,E.Delta(i,j)::ds,dels,E.Tensor(id,[tx])::es,done)=
if(j=tx) then distribute(change@[j],dels@ds,[] ,es ,done@[E.Tensor(id,[i])])
else distribute(change,ds,dels@[E.Delta(i,j)],E.Tensor(id,[tx])::es,done)
| distribute(change,E.Delta(i,j)::ds,dels,E.Field(id,[tx])::es,done)=
if(j=tx) then distribute(change@[j],dels@ds,[] ,es ,done@[E.Field(id,[i])])
else distribute(change,ds,dels@[E.Delta(i,j)],E.Field(id,[tx])::es,done)
| distribute(change,E.Delta(i,j)::ds,dels,E.Apply(E.Partial d,e)::es,done)=
108          let          let
109              fun distPart([],rest) =(0 ,rest)              val (c',b')=mkprobe(rewrite e1,rewrite e2)
110                  | distPart(p::pd,rest)=              in (case c'
111                      if(p=j) then (1,rest@[i]@pd)              of 1=> (changed:=true;b')
112                      else (distPart(pd,rest@[p]))              | _ => b'

val (change'',p')=distPart(d,[])
val x=print "in here "
in (case change''
of 0=>distribute(change, ds,dels@[E.Delta(i,j)], [E.Apply(E.Partial d, e)]@es,done)
|_=> distribute(change@[j], dels@ds,[], es,done@[E.Apply(E.Partial p', e)])
113              (*end case*))              (*end case*))
114          end          end
115            | E.Apply(E.Partial [],e1)              => e1
116                  (*          | E.Apply(E.Partial d1, e1)             =>
117          if(j=tx) then distribute(change@[j],dels@ds,[] ,es ,done@[E.Field(id,[i])])              let
118          else distribute(change,ds,dels@[E.Delta(i,j)],E.Field(id,[tx])::es,done)              val e2 = rewrite e1
119               *)                  val (c,e3)=mkapply(E.Partial d1,e2)
120                    val _= testp["\nafter apply:",P.printbody body,"-->",P.printbody e3]
| distribute(change,d,dels,e::es,done)=distribute(change,dels@d,[],es,done@[e])

val (dels,eps,es)=findDeltas([],[],p)
val (change,dels',done)=distribute([],dels,[],es,[])
val index=rmIndex(change,[],c)

121    in    in
122         (length change, E.Sum(index,E.Prod (eps@dels'@done)))                      (case c of 1=>(changed:=true;e3)| _ =>e3 (*end case*))
123    end    end
124            | E.Apply _                             => err " Not well-formed Apply expression"
125
126                (************** Field Terms **************)
127  (*Apply Sum*)          | E.Value _                             => err "Value before Expand"
128  fun mkApplySum(E.Apply(E.Partial d,E.Sum(c,e)))=(case e          | E.Img _                               => err "Img before Expand"
129      of E.Tensor(a,[])=>(1,E.Const 0.0)          | E.Krn _                               => err "Krn before Expand"
130      | E.Const _ =>(1,E.Const 0.0)              (************** Sum **************)
131      | E.Delta _ =>(1,E.Const 0.0)
132      | E.Value _ =>(1,E.Const 0.0)          | E.Sum([],e1)                           => (changed:=true;rewrite e1)
133      | E.Epsilon _ =>(1,E.Const 0.0)          | E.Sum(sx1,e1)                            => let
134                    val e2=rewrite e1
135      | E.Add l => (1,E.Add(List.map (fn e => E.Apply(E.Partial d, E.Sum(c,e))) l))                  val (c,e')=mkSum(sx1,e2)
136      | E.Sub(e2, e3) =>(1, E.Sub(E.Apply(E.Partial d, E.Sum(c,e2)), E.Apply(E.Partial d, E.Sum(c,e3))))                  val _= testp["\nafter mksum:\n\t",P.printbody body,"\n\t-->",P.printbody e2,"\n\t-->",P.printbody e']
137      | E.Conv (fid,alpha,tid, delta)=> let                  in
138          val e'=E.Conv(fid,alpha, tid, delta@d)                  (case c of 0 => e'|_ => (changed:=true;e'))
in (1,E.Sum(c,e')) end

| E.Prod [e1]=>(1,E.Apply(E.Partial d,E.Sum(c,e1)))
| E.Prod es'=> let
val y=print "in apply sum"
val (change,m)=reduceDelta(E.Sum(c,e))
val t=print(Int.toString(change))
val (sumc,es)=(case (change,m) of (0,_)=>(c,es')
| (_,E.Sum( c', E.Prod p)) =>(c',p)
(*end case*))
val (pre', dels,post)= filter(es,[],[],[])
val pre=pre'@dels
val x1= prodAppPartial(post,d)
in  (case x1
of E.Add a=> (1,E.Add(List.map (fn e =>  E.Sum(sumc,E.Prod(pre@[e]))) a))
| _ => (1,E.Sum(sumc, E.Prod(pre@[x1])))
(*end case*))
end
|_=>(0,E.Apply(E.Partial d,E.Sum(c,e)))
(* end case*))

(*Apply*)
fun mkApply(E.Apply(E.Partial d,e))=(case e
of E.Tensor(a,[])=>(1,E.Const 0.0)
| E.Const _ =>(1,E.Const 0.0)
| E.Delta _ =>(1,E.Const 0.0)
| E.Value _ =>(1,E.Const 0.0)
| E.Epsilon _ =>(1,E.Const 0.0)
| E.Conv (fid,alpha,tid, delta)=> let
val e'=E.Conv(fid,alpha, tid, delta@d)
in (1,e') end
| E.Add l => (1,E.Add(List.map (fn e => E.Apply(E.Partial d, e)) l))
| E.Sub(e2, e3) =>(1, E.Sub(E.Apply(E.Partial d, e2), E.Apply(E.Partial d, e3)))
| E.Div(e2, e3) =>(1, E.Div(E.Apply(E.Partial d, e2),  e3))
| E.Apply(E.Partial d2,e2)=>(1,E.Apply(E.Partial(d@d2), e2))
| E.Prod [e1]=>(1,E.Apply(E.Partial d,e1))
| E.Prod es=> let
val (pre,dels, post)= filter(es,[],[],[])
val (_,x)=mkProd(pre@[prodAppPartial(post,d)])
in (1,x) end
|_=>(0,E.Apply(E.Partial d,e))
(* end case*))

(*Sum Apply*)

fun matchEps(2,_,_,_)= 1 (*matched 2*)
| matchEps(num,_,_,[])=0
| matchEps(0,_,_,[eps])=0
| matchEps(num,[],rest,eps::epsx)=
matchEps(num,rest,[],epsx)
| matchEps(num,E.V p::px,rest,eps::epsx)=
if(p=eps) then (matchEps(num+1,rest@px,[],epsx))
else matchEps(num,px,rest@[E.V p], eps::epsx)
| matchEps(num,p::px,rest,eps)=
matchEps(num,px,rest,eps)

fun mkSumApply(E.Sum(c,E.Apply(E.Partial d,e)))=(case e
of E.Const _=>(1,E.Const 0.0)
| E.Tensor(_,[])=> (1,E.Const 0.0)
| E.Delta _ =>(1,E.Const 0.0)
| E.Value _ =>(1,E.Const 0.0)
| E.Epsilon _ =>(1,E.Const 0.0)
| E.Conv (fid,alpha,tid, delta)=> let
val e'=E.Conv(fid,alpha, tid, delta@d)
in (1,E.Sum(c,e')) end
| E.Apply(E.Partial d1,e2)=>(1,E.Sum(c,E.Apply(E.Partial(d@d1),e2)))
| E.Add l => (1,E.Add(List.map (fn e => E.Sum(c,E.Apply(E.Partial d, e))) l))
| E.Sub(e1, e2) => (1, E.Sub(E.Sum(c,E.Apply(E.Partial d, e1)), E.Sum(c,E.Apply(E.Partial d, e2))))

| E.Prod [e1]=>(1,E.Sum(c,E.Apply(E.Partial d,e1)))

| E.Prod(E.Tensor(a,[])::e2)=>(1, E.Prod[E.Tensor(a,[]),E.Sum(c,E.Apply(E.Partial d,E.Prod e2))])

| E.Prod es =>(let
fun prod (change,rest, sum,partial,[]) = (change,E.Sum(sum,E.Apply(E.Partial partial,E.Prod rest)))
| prod (change,rest, sum,partial,E.Epsilon(i,j,k)::ps)= let
val change'= matchEps(0,d,[],[i,j,k])
in (case change'
of 1 => (1,E.Const 0.0)
| _ =>prod(change,rest@[E.Epsilon(i,j,k)],sum,partial,ps)
(*end case*))
139              end              end
140          | prod (change,rest, sum,partial,E.Delta(i,j)::ps)=let              (*************Algebraic Rewrites Op1 **************)
141              fun applyDelPartial([],_)=(0,[])          | E.Op1(E.Neg,e1)                       => (case e1
142              | applyDelPartial(p::px,r)=              of E.Op1(E.Neg,e2)                  => rewrite e2
143                  if(j=p) then (1,r@[i]@px)              | E.B(E.Const 0)                    =>(changed:=true;zero)
144                  else  applyDelPartial(px,r@[p])              | _                                 => E.Op1(E.Neg,rewrite e1)
145                (*end case*))
146              val (change',px)=applyDelPartial(d,[])          | E.Op1(op1,e1)                         => E.Op1(op1,rewrite e1)
147                (*************Algebraic Rewrites Op2 **************)
148              in (case change'          | E.Op2(E.Sub,e1,e2)                        => (case (e1,e2)
149                  of 1 => (let val index=rmIndex([j],[],sum)              of (E.B(E.Const 0),_)                   => (changed:=true;setNeg(rewrite e2))
150                      in prod(1,rest, index,px, ps) end )              | (_,E.B(E.Const 0))                     => (changed:=true;rewrite e1)
151                  | _ => prod(change,rest@[E.Delta(i,j)], sum,partial, ps)              | _                                 => setSub(rewrite e1, rewrite e2)
152                  (*end case*)) end              (*end case*))
153            | E.Op2(E.Div,e1,e2)                        =>(case (e1,e2)
154          | prod (change,rest,sum, partial,e::es)= prod(change,rest@[e],sum,partial,es)              of (E.B(E.Const 0),_)                    => (changed:=true;zero)
155                |(E.Op2(E.Div,a,b), E.Op2(E.Div,c,d))   => rewrite(setDiv(setProd[a,d],setProd[b,c]))
156          in  prod(0,[],c, d, es)              |(E.Op2(E.Div,a,b), c)   =>  rewrite (setDiv(a, setProd[b,c]))
157                | (a,E.Op2(E.Div,b,c))                   => rewrite (setDiv(setProd[a,c],b))
158                |  _                        => setDiv(rewrite e1, rewrite e2)
end)
| _=>(0,E.Sum(c,E.Apply(E.Partial d,e)))
159          (* end case*))          (* end case*))
160                (*************Algebraic Rewrites Opn **************)
161    (*
162  (*Apply normalize to each term in product list  | E.Opn(E.Add,[E.Sum([(E.V 4,0,2)],E.Opn(E.Prod,[E.Tensor(0,[E.V 4,E.V 0]), E.Tensor(1,[E.V 4,E.V 1])])),E.Opn(E.Prod,[E.Tensor(2,[]),
163  or Apply normalize to tail of each list*)  E.Sum([(E.V 8,0,2)],E.Opn(E.Prod,[E.Tensor(0,[E.V 8,E.V 0]), E.Tensor(4,[E.V 8,E.V 1])]))])]) => let
164  fun normalize (Ein.EIN{params, index, body}) = let  val a = E.Tensor(0,[E.V 2,E.V 0])
165    val b = E.Tensor(1,[E.V 2,E.V 1])
166        val changed = ref false  val c = E.Tensor(4,[E.V 2,E.V 1])
167    val s = E.Tensor(2,[])
168        fun rewriteBody body = (case body  val add = E.Opn(E.Add,[b,E.Opn(E.Prod,[s,c])])
169               of E.Const _=> body  val prod= E.Sum([(E.V 2,0,2)],E.Opn(E.Prod,[a,add]))
170                | E.Tensor _ =>body  val _ =print(String.concat["\nMatched"])
171                | E.Field _=> body  in prod end
172                | E.Delta _ => body  *)
173                | E.Value _ =>body          | E.Opn(E.Add,es)          => let
174                | E.Epsilon _=>body              val (change,body')= mkAdd(List.map rewrite es)
| E.Conv _=>body

| E.Neg e => E.Neg(rewriteBody e)
| E.Add es => let val (change,body')= mkAdd(List.map rewriteBody es)
175                     in if (change=1) then ( changed:=true;body') else body' end                     in if (change=1) then ( changed:=true;body') else body' end
| E.Sub(a, E.Field f)=> (changed:=true;E.Add[a, E.Neg(E.Field(f))])
| E.Sub (a,b)=>  E.Sub(rewriteBody a, rewriteBody b)
| E.Div (a, b) => E.Div(rewriteBody a, rewriteBody b)
| E.Partial _=>body
| E.Krn(tid,deltas,pos)=> E.Krn(tid,deltas, (rewriteBody pos))
| E.Img(fid,alpha,pos)=> E.Img(fid,alpha, (List.map rewriteBody pos))

176
177                  (*************Product**************)                  (*************Product**************)
178                | E.Prod [e1] => rewriteBody e1          | E.Opn(E.Prod,[])                                 => err "missing elements in product"
179                | E.Prod((E.Add(e2))::e3)=>          | E.Opn(E.Prod,[e1])                               => rewrite e1
180                     (changed := true; E.Add(List.map (fn e=> E.Prod([e]@e3)) e2))          | E.Opn(E.Prod,[e1 as E.Op1(E.Sqrt,s1),e2 as E.Op1(E.Sqrt,s2)])=>
181                | E.Prod((E.Sub(e2,e3))::e4)=>              if(Eq.isBodyEq(s1,s2)) then (changed :=true;s1)
182                     (changed :=true; E.Sub(E.Prod([e2]@e4), E.Prod([e3]@e4 )))              else (*let
183                    val a=rewrite (E.Op1(E.Sqrt,s1))
184                | E.Prod((E.Div(e2,e3))::e4)=>                  val b=rewrite (E.Op1(E.Sqrt,s2))
185                  (changed :=true; E.Div(E.Prod([e2]@e4), e3 ))                  val  (_,d)=mkProd ([a,b])
186                    in d
187                | E.Prod(e1::E.Add(e2)::e3)=>                  end*)  prod2(e1, e2,[])
188                  (changed := true; E.Add(List.map (fn e=> E.Prod([e1,e]@e3)) e2))          (*************Product EPS **************)
189                | E.Prod(e1::E.Sub(e2,e3)::e4)=>          | E.Opn(E.Prod,(E.G(E.Epsilon e1)::ps))=> let
190                  (changed :=true; E.Sub(E.Prod([e1,e2]@e4), E.Prod([e1,e3]@e4 )))              val E.G(E.Epsilon(i,j,k))=E.G(E.Epsilon e1)
191                val eps1=E.G(E.Epsilon(i,j,k))
192                | E.Prod(E.Epsilon(i,j,k)::E.Apply(E.Partial d,e)::es)=>let              val p1=List.hd(ps)
193                   val change= matchEps(0,d,[],[i,j,k])              in (case ps
194                    of (E.Apply(E.Partial d,e)::es)=>let
195                        val change= G.matchEps(0,d,[],[i,j,k])
196                   in case (change,es)                   in case (change,es)
197                  of (1,_) =>(changed:=true; E.Const 0.0)                          of (1,_)    => (changed:=true; zero)
198                      | (_,[]) =>E.Prod[E.Epsilon(i,j,k),                          | _ => prod2(eps1, p1, es)
(rewriteBody (E.Apply(E.Partial d,e)))]
|(_,_)=> let
val a=rewriteBody(E.Prod([E.Apply(E.Partial d,e)]@ es))
val (_,b)=mkProd [E.Epsilon(i,j,k),a]
in b end
199                  end                  end
200                | E.Prod[(E.Epsilon(e1,e2,e3)), E.Tensor(_,[E.V i1,E.V i2])]=>                  | (E.Conv(V,alpha, h, d)::es)=>let
201                      if(e2=i1 andalso e3=i2) then (changed :=true;E.Const(0.0))                      val change= G.matchEps(0,d,[],[i,j,k])
202                      else body                      in case (change,es)
203                | E.Prod [E.Partial r1, E.Tensor(_,[])]=> (changed:=true;E.Const(0.0))                          of (1,_)    => (changed:=true; E.Lift zero )
204                | E.Prod [E.Partial r1,E.Partial r2]=>                          | (_,_)     => prod2(eps1, p1 ,es)
(changed:=true;E.Partial(r1@r2))

| E.Prod(E.Partial r1::E.Partial r2::p)=>
(changed:=true;E.Prod([E.Partial(r1@r2)]@p))
| E.Prod(E.Sum(c1,E.Prod(E.Epsilon e1::es1))::E.Sum(c2,E.Prod(E.Epsilon e2::es2))::es)=>let
val (change,e,rest)=epsToDels(E.Sum(c1@c2, E.Prod([E.Epsilon e1, E.Epsilon e2]@es1@es2@es)))
in (case (change,e, rest)
of (1,[e1],_)=> (changed:=true;e1)
| _=>let
val e1=rewriteBody(E.Sum(c1,E.Prod(E.Epsilon e1::es1)))
val es'=rewriteBody(E.Prod(E.Sum(c2,E.Prod(E.Epsilon e2::es2))::es))
val (_,e)=(case es' of E.Prod p=>mkProd([e1]@p)
|_=> mkProd([e1]@e)
(*end case*))
in e
end
(*end case*))
end
| E.Prod[e1,e2]=> let val (_,b)=mkProd[rewriteBody e1, rewriteBody e2] in b end
| E.Prod(e::es)=>let
val e'=rewriteBody e
val e2=rewriteBody(E.Prod es)
val(_,b)=(case e2
of E.Prod p'=> mkProd([e']@p')
|_=>mkProd [e',e2])
in b
205                     end                     end
206                    | _  => (case (G.epsToDels(eps1::ps))
207                (**************Apply**************)                      of (1,e,[],_,_)       => (changed:=true;e)(* Changed to Deltas*)
208                        | (1,e,sx,_,_)        => (changed:=true;E.Sum(sx,e))
209                (* Apply, Sum*)                      | (_,_,_,_,[])        =>  body
210                | E.Apply(E.Partial d,E.Sum e)=>let                      | (_,_,_,epsAll,[r]) =>  E.Opn(E.Prod,epsAll@[rewrite r])
211                      val s'=rewriteBody(E.Sum  e)                      | (_,_,_,epsAll,rest) => (case (rewrite(E.Opn(E.Prod, rest)))
212                      val (c, e')=(case s'                          of E.Opn(E.Prod, ps')=> E.Opn(E.Prod, epsAll@ ps')
213                          of E.Sum e1=> mkApplySum(E.Apply(E.Partial d,s'))                          | t => (changed:=true; E.Opn(E.Prod,epsAll@[t])))
| _=>(0, E.Apply(E.Partial d, s'))
214                          (*end case*))                          (*end case*))
in (case c
of 1=>(changed:=true;e')
|_=> e'
(*end case*))
end

| E.Apply(E.Partial [],e)=> e
| E.Apply(E.Partial p,E.Probe(E.Conv(fid,alpha,tid,d),x))=>
(changed:=true;E.Probe(E.Conv(fid,alpha,tid,d@p),x))
| E.Apply(E.Partial p,E.Conv(fid,alpha,tid,d))=>
(changed:=true;E.Conv(fid,alpha,tid,d@p))
| E.Apply(E.Partial p, e)=>let

val body'=E.Apply(E.Partial p, rewriteBody e)
val (c, e')=mkApply(body')
in (case c
of 1=>(changed:=true;e')
| _ =>e') end

| E.Apply(e1,e2)=>((E.Apply(rewriteBody e1, rewriteBody e2))
)

(************** Sum *****************)
| E.Sum([],e)=> (changed:=true;rewriteBody e)
| E.Sum(_,E.Const c)=>(changed:=true;E.Const c)
| E.Sum(c,(E.Add l))=> (changed:=true;E.Add(List.map (fn e => E.Sum(c,e)) l))
| E.Sum(c,E.Sub(e1,e2))=>(changed:=true; E.Sub(E.Sum(c,e1),E.Sum(c,e2)))
| E.Sum(c,E.Div(e1,e2))=>(changed:=true; E.Div(E.Sum(c,e1),E.Sum(c,e2)))
| E.Sum(c, E.Prod(E.Const e::es))=>(changed:=true;E.Prod[E.Const e,E.Sum(c, E.Prod es)])

| E.Sum(c, E.Prod(E.Value v::es))=>(changed:=true; E.Prod [E.Value v, E.Sum(c, E.Prod es)])
| E.Sum(c, E.Prod(E.Tensor(id,[])::es))=> (changed:=true;E.Prod [E.Tensor(id,[]), E.Sum(c, E.Prod es)])
| E.Sum(c,E.Prod(E.Epsilon eps1::E.Epsilon eps2::ps))=>
let val (i,e,rest)=epsToDels(body)
in (case (i, e,rest)
of (1,[e1],r) =>(changed:=true;e1)
|(0,eps,[])=>body
|(0,eps,rest)=> let
val p'=rewriteBody(E.Prod rest)
val p''= (case p' of E.Prod p=>p |e=>[e])
val(_,b)= mkProd (eps@p'')
in E.Sum(c,b) end
|_=>body
215                      (*end case*))                      (*end case*))
216                     end                     end
217            | E.Opn(E.Prod,E.Sum(c1,e1)::E.Sum(c2,e2)::es)=>(case (e1,e2,es)
218                of (E.Opn(E.Prod,E.G(E.Epsilon e1)::es1),E.Opn(E.Prod,E.G(E.Epsilon e2)::es2),_) =>
219                    (case G.epsToDels([E.G(E.Epsilon e1), E.G(E.Epsilon e2)]@es1@es2@es)
220                        of (1,e,sx,_,_)=> (changed:=true; E.Sum(c1@c2@sx,e))
221                        | (_,_,_,_,_)=>
222                            let
223                                val eA= E.Sum(c1,setProd(E.G(E.Epsilon e1)::es1))
224                                val eB= E.Sum(c2,setProd(E.G(E.Epsilon e2)::es2))
225                            in prod2(eA, eB, es) end
226
| E.Sum(c1,E.Prod(E.Epsilon eps1::E.Sum(c2,E.Prod(E.Epsilon eps2::s2))::ps))=>let
val (i, e, rest)=epsToDels(E.Sum(c1@c2, E.Prod([E.Epsilon eps1, E.Epsilon eps2]@ s2@ps)))
in (case (i,e,rest)
of (1,[e1],_) =>(changed:=true; e1)
|_ => E.Sum(c1,rewriteBody(E.Prod(E.Epsilon eps1::E.Sum(c2,E.Prod(E.Epsilon eps2::s2))::ps)))
227                      (* end case*))                      (* end case*))
228                    end                  | _  => prod2(E.Sum(c1,e1),E.Sum(c2,e2),es)
229                (*end case*))
230                | E.Sum(c,E.Prod(E.Delta d::es))=>let          | E.Opn(E.Prod,E.G(E.Delta d)::es) => let
231                      val (change,a)=reduceDelta(body)              val (pre',eps, dels,post)= filterGreek(E.G(E.Delta d)::es)
232                val _= testp["\n\n Reduce delta--",P.printbody(body)]
233                val (change,a)=G.reduceDelta(eps, dels, post)
234                val _= testp["\n\n ---delta moved--",P.printbody(a)]
235                      in (case (change,a)                      in (case (change,a)
236                  of (0, _)=> E.Sum(c,rewriteBody(E.Prod([E.Delta d]@es)))                  of (0, _)=>  prod2(E.G(E.Delta d), List.hd(es) , List.tl(es))
237                          | (_, E.Prod p)=>let                  | (_, E.Opn(E.Prod, p))=>let
238                              val (_, p') = mkProd p                              val (_, p') = mkProd p
239                              in (changed:=true;p') end                              in (changed:=true;p') end
240                          | _ => (changed:=true;a )                   | _ => raise Fail"impossible"
241                          (*end case*))                          (*end case*))
242                      end                      end
243          | E.Opn(E.Prod,[e1,e2])=> let
244                val (_,b)=mkProd[rewrite e1, rewrite e2]
245                | E.Sum(c,E.Apply(E.Partial p,e))=>let              in b end
246                      val (change,exp)=mkSumApply(body)        | E.Opn(E.Prod,e1::es)=>let
247                      val exp'=(case change              val e'=rewrite e1
248                          of 1=> (changed:=true;exp)              val e2=rewrite(setProd es)
249                          | _ => E.Sum(c,rewriteBody(E.Apply(E.Partial p,e))))              val(_,b)=(case e2
250                      in exp' end                  of E.Opn(Prod, p')=> mkProd([e']@p')
251                    |_=>mkProd [e',e2])
252                in b end
| E.Sum(c,e)=>E.Sum(c,rewriteBody e)

(*Probe*)
| E.Probe(E.Sum(c,s),x)=>(changed:=true;E.Sum(c,E.Probe(s,x)))
| E.Probe(E.Neg e1,x)=>(changed:=true;E.Neg(E.Probe(e1,x)))
| E.Probe(E.Add es,x) =>
| E.Probe(E.Sub (a,b),x)=>
(changed:=true;E.Sub(rewriteBody(E.Probe(a,x)), rewriteBody(E.Probe(b,x))))
| E.Probe(E.Div (a,b),x) =>
(changed:=true;E.Div(rewriteBody(E.Probe(a, x)),b))
| E.Probe(E.Prod p, x)=>let
val (p',x')= (rewriteBody (E.Prod p), rewriteBody x)
fun  probeprod([],rest) =
(print "err-Did not find field/Conv"; body)
| probeprod(E.Const c::es,rest)=
(changed:=true;probeprod(es,rest@[E.Const c]))
| probeprod(E.Tensor t::es,rest)=
(changed:=true;probeprod(es,rest@[E.Tensor t]))
| probeprod(E.Krn e::es, rest)=
(changed:=true;probeprod(es, rest@[E.Krn e]))
| probeprod(E.Delta e::es, rest)=
(changed:=true;probeprod(es, rest@[E.Delta e]))
| probeprod(E.Value e::es, rest)=
(changed:=true;probeprod(es, rest@[E.Value e]))
| probeprod(E.Epsilon e::es, rest)=
(changed:=true;probeprod(es, rest@[E.Epsilon e]))
| probeprod(E.Partial e::es, rest)=
(changed:=true;probeprod(es, rest@[E.Partial e]))
| probeprod(E.Field f::es,rest)=
(changed:=true;E.Prod(rest@[E.Probe(E.Field f, x')] @es))
| probeprod(E.Conv f::es,rest)=
(changed:=true;E.Prod(rest@[E.Probe(E.Conv f, x')] @es))
| probeprod(E.Prod p::es , rest)=
(changed:=true;probeprod(p@es,rest))
| probeprod(_,[])=body
| probeprod(e1::es, rest)=let
val e'= rewriteBody(E.Prod(e1::es))
val e''= rewriteBody(E.Probe(e',x'))
in  (changed:=true;E.Prod(rest@[e'']))
end
in (case p'
of E.Prod pro=>probeprod(p,[])
|_=> E.Probe(p',x')
253                      (*end case*))                      (*end case*))
254                  end                  end
| E.Probe(u,v)=>  (E.Probe(rewriteBody u, rewriteBody v))
(*end case*))
255
fun loop(body ,count) = let
val body' = rewriteBody body
256
257                 (* val y=(print "Counter:";print(Int.toString(count));print"\n")*)      val _=testp["\n******** Start Normalize: \n",P.printerE ee,"\n*****\n"]
258        fun loop(body ,count) = let
259            val _= (concat["\n N =>",Int.toString(count)])
260            val body' = rewrite body
261            val _=(EqualEin.boolToString(EqualEin.isBodyEq(body,body')))
262              in              in
263                if !changed                if !changed
264                  then (changed := false ;loop(body',count+1))                  then (changed := false ;loop(body',count+1))
# Line 554  Line 266
266              end              end
267
268      val (b,count) = loop(body,0)      val (b,count) = loop(body,0)
269      (*val j=(print "Final Counter:";print(Int.toString(count));print"\n")*)      val _ =testp["\n Out of normalize \n",P.printbody(b),
270            "\n    Final CounterXX:",Int.toString(count),"\n\n"]
271      in      in
272                  (Ein.EIN{params=params, index=index, body=b},count)                  (Ein.EIN{params=params, index=index, body=b},count)
273      end      end
274  end  end
275
276

277  end (* local *)  end (* local *)

Legend:
 Removed from v.2508 changed lines Added in v.3678

 root@smlnj-gforge.cs.uchicago.edu ViewVC Help Powered by ViewVC 1.0.0